Where and why is landscape considered valuable? Societal actors' perceptions of ecosystem services across Bavaria (Germany). Issue 1 (31st December 2023) - Küchen, Lisa; Schmitt, Thomas M.; Riebl, Rebekka; Hänsel, Maria; Steinbauer, Manuel J.; Fricke, Ute; Redlich, Sarah; Koellner, Thomas
ABSTRACT: Balancing the demand for ecosystem services (ES) with available supply is one key challenge for decision making in sustainable landscape management. ES demand is context-specific. Therefore, the assessment of perceptions articulated by multiple societal actors in different regions can help to identify differences and commonalities in predominant preferences for landscapes and their ES. The goal of this study was to investigate four societal actor groups (citizens, farmers, foresters, nature managers) in 12 study regions across Bavaria, Germany, with respect to their valuation of landscapes and ES provided by certain landscape elements. The 2, 438 participants mapped specific locations and selected landscape elements that they perceived as valuable, and further elaborated on this value in open statements. We applied qualitative content analysis, word frequency analysis, spatial location-density analysis, and statistical testing. The perceived value of landscape elements for ES differed across actor groups and regions. Preference for landscape elements was driven by topography and land use and was significantly associated with actor groups. The most apparent differences occurred between farmers and nature managers. Generally, participants preferred forests, water bodies, natural landscapes, and distinct geographical structures. The landscape was mostly valued for its habitat, diverse wildlife, recreational purposes, climate-regulating functions, and provisioning of water and food. We conclude that, although differences exist among societal actors, the study respondents highly valued the importance of functioning and diverse ecosystems. The high perceived value for many ecosystem services and species protection suggests that ambitious policy measures are supported by different societal actors.